Dimensions of Multinational Enterprises - Maria - Ramona Sarbu (CES Working Papers, 2015)
Capital, creating new jobs, innovation, advanced technologies and the know-how transfer to local firms, human resources with a high level of training, effective management capacity, providing the necessary inputs for the evolution of the activity under the best conditions of efficiency, the access of local consumers to a variety of products and services are the main advantages that multinational enterprises (MNEs) bring in the countries where they expand their activities, with a significant impact on economic activities, between national economies. The purpose of this study is the analysis of the main non-financial multinationals in the world, based on the assets held abroad and depending on the transnationality index (TNI) in 2013. In order to achieve the purpose of the current paper we employed data from UNCTAD database and the World Investment Report (WIR) from 2015. Information on multinationals ranked by foreign assets according to the World Investment Report in 2015 show that, based on the TN, European multinationals, such as the ones in France, Italy, Germany and Norway, have a higher transnationality index compared to multinationals from larger countries, such as the US and China. Among the top 10 European multinationals, the transnationality index reached an average of 55 % in 2013.
Keywords: F23; M14; 330; MNEs; TNI; social responsibilities